2023
DOI: 10.1002/smll.202302765
|View full text |Cite
|
Sign up to set email alerts
|

Aflibercept Loaded Eye‐Drop Hydrogel Mediated with Cell‐Penetrating Peptide for Corneal Neovascularization Treatment

Jianan Zhou,
Yuting Cai,
Tingting Li
et al.

Abstract: Corneal neovascularization (CoNV) is a major cause of visual impairment worldwide. Currently, available treatment options have limited efficacy and are associated with adverse effects due to biological barriers and clearance mechanisms. To address this challenge, a novel topical delivery system is developed—Gel 2_1&Eylea—an aflibercept‐loaded eye‐drop hydrogel mediated with cell‐penetrating peptide 1. Gel 2_1&Eylea demonstrates superior membrane permeability, increased stability, and prolonged drug ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Our experiments have shown that multiple cell lines can be cultured within the peptide hydrogel with high cell viability, enabling cells to grow into complex morphology. As a result, the peptide hydrogel developed shows great promise as a versatile tool for a variety of biomedical applications, including drug release, drug screening, and tissue engineering. , …”
Section: Discussionmentioning
confidence: 99%
“…Our experiments have shown that multiple cell lines can be cultured within the peptide hydrogel with high cell viability, enabling cells to grow into complex morphology. As a result, the peptide hydrogel developed shows great promise as a versatile tool for a variety of biomedical applications, including drug release, drug screening, and tissue engineering. , …”
Section: Discussionmentioning
confidence: 99%